(untitled) (American Journal of Islam and Society, 1987)
I. Scientific Justification for the Islamization of Knowledge The need for the Islamization of knowledge as a means to revive the leadership of the Islamic Umma in the world has been explained over a period of many years by Dr. ‘AbdulHamid ’AbuSulayman. A clear conceptualization of this Islamization, based on Tawhid, was first proposed by Professor Isma‘il Raji al Faruqi 1982 and presented as both a theoretical paradigm and a practical scientific research program. Both the theory and program have been attacked as unscientific, because they are not descriptive but rather are normative. They call for the reorganization of knowledge into a new framework that does not grow out of the old secular framework of modem thought. Furthermore, Professor al Faruqi’s paradigm and praxis call for the pursuit of value-laden goals, that is, for the “ought-to-be” not only as an end in itself but as a guide and methdology for the study of what “is.” A thesis of this article is that the whole concept known as “Islamization of Knowledge,” developed by Drs. ’AbuSulayman and al Faruqi, is thoroughly scientific in the sense used by modem historians and philosophers of science. Theoreticians in the Islamization of Knowledge claim they are laying the ...